Rapid internalization of the transferrin receptor in K562 cells is triggered by ligand binding or treatment with a phorbol ester. - Klausner, R D (1984)
Treatment of human K562 cells with 4 beta-phorbol 12-myristate 13-acetate (PMA) resulted in an approximately 50% reduction in cell surface transferrin receptors within 30-45 min as judged by binding of both ligand and anti-receptor antibody. The affinity of the remaining surface receptors for diferric transferrin appeared to be unaltered. The time-dependent loss in transferrin receptors was also dependent upon PMA concentration, with a half-maximal effect observed at approximately 1 nM. The kinetic parameters for the binding, internalization, intracellular residency, and recycling of 125I-labeled transferrin were unchanged by PMA treatment, as were the rate and extent of internalization of anti-receptor antibody. Moreover, despite the decrease in surface receptors, uptake of 59Fe from transferrin proceeded at a rate comparable to that seen in untreated cells. Accounting for this observation was the fact that ligand induced a reduction in surface receptors in untreated but not PMA-treated cells. Quantitative immunoprecipitation of transferrin receptors from surface-iodinated K562 cells revealed that little receptor internalization occurred in untreated cells in the absence of ligand, but internalization of ligand-occupied receptors in these cells was readily detected. In contrast, PMA treatment resulted in the rapid internalization of surface receptors irrespective of occupancy. Thus, binding of ligand appeared to trigger the internalization of receptors that were relatively static in their unoccupied state, and a signal for receptor internalization was also provided by PMA treatment. The possibility that this signal involves phosphorylation of the transferrin receptor is discussed.